THE IMPACT OF TAX INCENTIVES ON THE PERFORMANCE OF THE CONSTRUCTION SECTOR IN THE CONTEXT OF THE COVID-19 PANDEMIC - Maria Zenovia GRIGORE; Iuliana UȚĂ (Challenges of the Knowledge Society)
The construction sector plays a key role in the economic development of a country, providing not only essential infrastructure, but also many jobs. In this context, the Romanian government has implemented in 2019 a series of fiscal measures aimed at stimulating growth and ensuring the financial sustainability of this crucial segment. The objective of this paper is to establish whether wage tax reductions for construction employees have contributed to economic growth, whether these tax incentives have provided the necessary support for the pursuit of the construction sector business during the Covid-19 pandemic and to what extent the managers of companies in this sector have been able to protect and even develop their business under these conditions. Macroeconomic analysis of the construction sector in Romania based on data provided by the National Institute of Statistics shows that these tax incentives have had a positive impact on the activity of construction companies. Annual increases in turnover, average number of employees and number of companies in the construction sector have occurred in each year of application of the tax facilities, although the COVID-19 pandemic slowed down the pace of growth in 2020 and 2021. Even though many firms closed down or became insolvent due to the pandemic in 2020 and 2021, the construction sector in Romania generated the highest share of Gross Value Added (GVA) compared to the rest of the EU in 2022. The analysis carried out in the second part of this paper focused on the financial performance of five companies in the specialised construction sector (NACE code 4399) and showed significant increases in profitability and labour productivity in the period 2019-2022. The managers of these companies took full advantage of the tax facilities and managed to develop their business during this period, securing a stable position in the Romanian construction market.